NOISE POLLUTION IN MAIZE MILLING SMES - Elias, Erasto; Majaja, Bashira A; Ibrahim, Said; Kizima, Emmanuel G. R (Tanzania Journal of Engineering and Technology, 2017)
Maize milling SMEs emit high levels of noise which can have adverse effects on human beings and therefore require controlling. This paper reports on a study that involved assessment and measurement of noise level in maize milling SMEs in DSM and Morogoro urban, gathering opinions of workers and the neighbouring population on noise problems, and suggesting solutions for noise control. Noise measurements in 41 SMEs were recorded from 89-103 dBA in DSM and 92-103 dBA in Morogoro near the milling machines. These values were higher than the safe level of 85 dBA for 8 hours working shift. Measurement also indicated high noise in the immediate neighbourhood of the milling plants. Machine operators and neighbours indicated health problems which could be a result of machine noise. Causes of high noise were identified to include loose or untightened machine parts, improper installation of machine system, use of worn out machine bearings, and the use of improperly designed and unbalanced milling hammers. Possible administrative and technical solutions for these problems were suggested. It is concluded from this study that most of maize milling SMEs produce high noise which is indeed pollutant to workers and the neighbouring population. Therefore, it is important to implement the suggested administrative and technical solutions to minimise this problem.